DOP34 Disease activity patterns during the first 5 years after diagnosis in children with ulcerative colitis: a population-based study. (25th January 2019) - Aloi, M; Bramuzzo, M; Norsa, L; Arrigo, S; Distante, M; Miele, E; Agrusti, A; Romano, C; Giobbi, C; Panceri, R; D'Antiga, L; Cucchiara, S; et al.
Abstract: Background: The aim of this study was to define clusters of disease activity of paediatric UC in a population-based inception cohort during the first 5 years after diagnosis and to identify prognostic risk factors based on findings at the diagnosis and in the first 6 months after. Methods: All UC patients from SIGENP IBD registry and a follow-up of at least 5 years were included. Patients with incomplete data (disease location, hospitalisations, endoscopy, PUCAI, medication use, surgery) were excluded. Active disease was defined for each yearly semester as follows: clinical activity (PUCAI>35); endoscopic activity (Mayo>1); hospitalisation; surgery; need for treatment escalation. Formula-based clusters were then generated based on five previously published activity patterns in adults. 1 Prediction models were created based on clinical, endoscopic, and laboratory findings at the diagnosis and at 6-month follow-up. Results: Two hundred and twenty-six patients were identified (53% F; median age 11, IQR 7–13). One hundred nine (48%) had a moderate-to-severe disease at the diagnosis. One hundred twenty-seven (53%) presented with a pancolitis, 29 (13%) with an extensive colitis, 24 (14%) with a left-sided colitis, and 36 (16%) with a proctitis. Clusters of disease activity are shown in Figure 1. Ulcerative colitis was classified as moderate–severe chronically active in 19% of patients ( N = 42), chronic-intermittent in 14% ( N = 31), while in 33% ( N = 75) the disease was classified as quiescent. Overall, 57% of the entire population ( N = 129) had an active UC in the first 2 years after the diagnosis, then a sustained remission. A high CRP (OR 3.79; 95% CI 1.28–11.2) and platelet count (OR 3.41; 95% CI 1.17–9.93) at the diagnosis were positively associated with a chronically active disease at follow-up, while an endoscopic recurrence at 6 months was negatively associated with a quiescent course thereafter (OR 0.37; 95% CI 0.13–0.96). Eight per cent of patients needed surgery at the end of the follow-up, none in the quiescent group ( p = 0.04). Conclusions: More than one-third of paediatric patients with UC present a chronically active or chronic intermittent disease course during the first 5 years after the diagnosis. A significant group of patients has an active disease in the first 2 years and a sustained remission thereafter. Interestingly, about 30% of patients experience a disease flare at the diagnosis followed by a quiescent disease course in the next 5 years of follow-up. Abstract DOP034 Clusters of disease activity Reference 1. Henriksen M, Jahnsen J, Lygren I, et al . Ulcerative colitis and clinical course: results of a 5-year population-based follow-up study (The IBSEN Study). Inflamm Bowel Dis 2006;12:543–50.